Studying the Key Intermediate of RNA Autohydrolysis by Cryogenic Gas‐Phase Infrared Spectroscopy. Issue 19 (24th March 2022) - Greis, Kim; Kirschbaum, Carla; Taccone, Martín I.; Götze, Michael; Gewinner, Sandy; Schöllkopf, Wieland; Meijer, Gerard; von Helden, Gert; Pagel, Kevin
Abstract: Over the course of the COVID‐19 pandemic, mRNA‐based vaccines have gained tremendous importance. The development and analysis of modified RNA molecules benefit from advanced mass spectrometry and require sufficient understanding of fragmentation processes. Analogous to the degradation of RNA in solution by autohydrolysis, backbone cleavage of RNA strands was equally observed in the gas phase; however, the fragmentation mechanism remained elusive. In this work, autohydrolysis‐like intermediates were generated from isolated RNA dinucleotides in the gas phase and investigated using cryogenic infrared spectroscopy in helium nanodroplets. Data from both experiment and density functional theory provide evidence for the formation of a five‐membered cyclic phosphate intermediate and rule out linear or six‐membered structures. Furthermore, the experiments show that another prominent condensed‐phase reaction of RNA nucleotides can be induced in the gas phase: the tautomerization of cytosine. Both observed reactions are therefore highly universal and intrinsic properties of the investigated molecules. Abstract : RNA autohydrolysis is a generic phenomenon in solution and proceeds via a 2′, 3′‐cyclic nucleotide intermediate. Cryogenic infrared spectroscopy in combination with DFT calculations show that the structure of c ‐fragments generated by the dissociation of RNA dinucleotides in the gas phase is equal to the key intermediate of RNA autohydrolysis. Furthermore, the data show that the nucleobase in cytidine phosphate readily tautomerizes in the gas phase.